Advancing Internationalization through Faculty Publication of their Experiences in Internationalizing the Curriculum at Historically Black Colleges and Universities (Comparative & International Education Series, 2021)
This chapter investigates how higher education institutions and faculty members at Historically Black Colleges and Universities and non-Historically Black Colleges and Universities have advanced internationalization of the institution through internationalization of the curriculum. The framework for understanding such faculty advancement of internationalization of the curriculum is found in the literature over time and in understanding contexts of instructional design, institutional internationalization, and faculty development. The findings show that Historically Black Colleges and Universities were late in promoting and implementing internationalization of the curriculum, however, publication of their faculty experiences in internationalization of the curriculum is shown to be unique. The conclusions show that faculty who publish their experience in internationalization of the curriculum may serve as disciplinary examples, motivation, and provide rationales and guidance for further engagement. Their publications also show that international and global learning goals and outcomes can potentially serve their students in the global employment marketplace.